2004
DOI: 10.1007/s00792-004-0401-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychrophilic Pseudomonas syringae requires trans-monounsaturated fatty acid for growth at higher temperature

Abstract: A psychrophilic bacterium, Pseudomonas syringae (Lz4W) from Antarctica, was used as a model system to establish a correlation, if any, between thermal adaptation, trans-fatty acid content and membrane fluidity. In addition, attempts were made to clone and sequence the cti gene of P. syringae (Lz4W) so as to establish its characteristics with respect to the cti of other Pseudomonas spp. and also to in vitro mutagenize the cti gene so as to generate a cti null mutant. The bacterium showed increased proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Southern analysis using genomic DNA of CSM1 (one of the cold-sensitive mutants) and ␣-32 P-labeled pOT182 (35,36) showed that CSM1 produced two bands, confirming that a single copy of the transposon was integrated (data not shown). The disrupted gene was identified by inverse PCR (46) using 35 cycles and transposon-specific outward primers (primers Ash 1 and Ash 3 for upstream regions and primers Ash 1 and Ash 2 for downstream regions) ( Table 2).…”
Section: Generation Of Cold-sensitive Mutants Psychrophilic Pseudomomentioning
confidence: 70%
See 3 more Smart Citations
“…Southern analysis using genomic DNA of CSM1 (one of the cold-sensitive mutants) and ␣-32 P-labeled pOT182 (35,36) showed that CSM1 produced two bands, confirming that a single copy of the transposon was integrated (data not shown). The disrupted gene was identified by inverse PCR (46) using 35 cycles and transposon-specific outward primers (primers Ash 1 and Ash 3 for upstream regions and primers Ash 1 and Ash 2 for downstream regions) ( Table 2).…”
Section: Generation Of Cold-sensitive Mutants Psychrophilic Pseudomomentioning
confidence: 70%
“…P. syringae was mutagenized with a Tn5 transposon-based suicide plasmid vector (pOT182) (35,42), and cold-sensitive mutants were identified based on their inability to grow or their delayed growth on plates incubated at 4°C for 1 week. Growth characteristics were also analyzed using a UV-visible spectrophotometer (Shimadzu, Kyoto, Japan) (36,37).…”
Section: Generation Of Cold-sensitive Mutants Psychrophilic Pseudomomentioning
confidence: 99%
See 2 more Smart Citations
“…For biochemical tests, cultures were grown at 22 uC on marine agar 2216 and tests were performed as described by Baumann et al (1984) and Smibert & Krieg (1994) potassium chloride and 0?028 g ferrous sulphate, supplemented with 0?2 % of the filter-sterilized carbon source (Romanenko et al, 2003). Fatty acid methyl esters were prepared from cells grown at 22 u C for 48 h according to the method of Sato & Murata (1988) and analysed as described by Kiran et al (2004). The modified method of Bligh & Dyer (1959) was employed to extract polar lipids and molybdenum blue reagent was used to detect lipids containing phosphate esters.…”
mentioning
confidence: 99%